2006
DOI: 10.1002/chin.200607165
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design, Synthesis, and Hypoglycemic and Hypolipidemic Activities of Novel Pyrimidine Derivatives Having Thiazolidinedione.

Abstract: Thiazolidinedione. -A variety of novel pyrimidine derivatives having a thiazolidinedione moiety [cf. (X), (XI)] is synthesized and evaluated for their antidiabetic activity. Derivatives (Xc) and (Xd) exhibit considerably more potent biological activities than the reference compounds rosiglitazone and pioglitazone. -(LEE, H. W.; KIM, B. Y.; AHN, J. B.; KANG, S. K.; LEE, J. H.; SHIN, J. S.; AHN, S. K.; LEE, S. J.; YOON, S. S.; Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 1 publication
1
26
0
Order By: Relevance
“…Our results showed the antileishmanial activity of the synthetic compounds were in consistence with previous results showed that hetero-cyclic compounds were potent anthelmintic, anti-fungal and anti-malarial agents [10][11][12][13][14][15][16] …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results showed the antileishmanial activity of the synthetic compounds were in consistence with previous results showed that hetero-cyclic compounds were potent anthelmintic, anti-fungal and anti-malarial agents [10][11][12][13][14][15][16] …”
Section: Discussionsupporting
confidence: 86%
“…Hetero cyclic compounds exhibit anthelmintic, anti HIV activity and hypoglycemic activity [9], antimicrobial, analgesic [10,11], against herpes simplex virus type-1 (HSV-1) and hepatitis-A virus (HAV), serotonin 5-HT6 receptor antagonist [12], antitumor activity and anticancer activity [13]. Thiazolopyrimidines have hypoglycemic, hypolipidemic, anti-diabetic, [14] and antimalarial [15,16]. As an extension of our ongoing studies, the objective of the present work is to synthesize new compounds and evaluates them both in vitro and in vivo for their anti-protozoal activities against experimental cutaneous Leishmaniasis in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Perkin condensation (Lee et al, 2005) of aryl aldehyde 1 with 4-hydroxyphenyl acetic acid 2 in the presence of acetic anhydride and triethylamine yielded 3-Aryl-2-(4-hydroxyphenyl)-acrylic acid 3. Esterification of this substituted acid followed by condensation with 4-fluorobenzaldehyde in the presence of sodium hydride in dimethyl formamide at 80°C for 18 h yielded 3-Aryl-2-[4-(4-formylphenoxy)-phenyl]-acrylic acid alkyl ester 5.…”
Section: Chemistrymentioning
confidence: 99%
“…Their different biological activities were reported [1,2]. Among the most important biological and pharmacological activities of both heterocyclic pharmacophoric moieties are: antihyperglycemic [3,4], antibacterial [5][6][7][8][9], antifungal [10,11], antiinflammatory [12][13][14][15][16][17], cyclooxygenase and lipoxygenase inhibitors [18,19], anticonvulsants [20,21], antitumor [22], antioxidant [23] and several other activities [1,2].…”
Section: Introductionmentioning
confidence: 99%